When the pound in people’s pocket matters: how changes to personal financial circumstances affect party choice - Tilley, James; Neundorf, Anja; Hobolt, Sara (Wiley, 2018)
In this paper we revisit the often disregarded ‘pocketbook voting’ thesis that suggests that people evaluate governments based on the state of their own finances. Using data from the British Household Panel Survey over the last 20 years, we measure changes in personal financial circumstances and show that the ‘pocketbook voting’ model works. Crucially, we also argue that the ability to attribute responsibility for these changes to the government matters. People respond much more strongly to changes in their own finances that are linked to government spending, such as welfare transfers, than to similar changes that are less clearly the responsibility of elected officials, such as lower personal earnings. We conclude that pocketbook voting is a real phenomenon, but that more attention should be paid to how people assign credit and blame for changes in their own economic circumstances.